INOVASI PEMANFAATAN LIMBAH KULIT PISANG SEBAGAI PRODUK PANGAN SEHAT: WORKSHOP PEMBERDAYAAN MASYARAKAT DESA DURAJAYA CIREBON - Cory Vidiati; Rosidah Rosidah; Fadiyah Putri Nur Habibah; Aldi Musthofainal Ahyar; Agus Rahmanto; Nabila Janan; Ayu Afika; Tasya Alifia; Ripdatul Maula; Rita Hernawati; Nurhalimah Ramadhani; Esa Negarawati; Rina Ari Pratiwi; Fika Alimna; Alifa Alifa (DEVELOPMENT: Journal of Community Engagement, 2026)
Banana peel waste in rural areas stays an unresolved environmental problem, even though peels contain useful nutrients like fiber, vitamins, and antioxidants. Durajaya Village in Cirebon Regency is among the largest banana transit centers, producing large volumes of peel waste every day. This community program aimed to improve residents' skills, including people with disabilities, in turning banana peels into nuggets as a potential home-based business. The program covered three stages: preparation, implementation, and evaluation, using a practical training method. Participants learned about the nutritional value of banana peels, safe processing techniques, and recipe ideas. Thirty-five people joined, including PKK mothers, local youth, and individuals with disabilities. About 90 percent of participants successfully made banana peel nuggets on their own, with good taste and a clear grasp of the nutritional benefits. Follow-up evaluation showed some participants had already used the product at home and considered it a small business option. The program boosted skills, raised awareness about organic waste use, and supported disability group involvement in productive economic activities. One limitation was that the final products were not tested in a laboratory for nutritional content.